PERAN MEDIA SOSIAL TERHADAP PERSEPSI DAN MINAT BELI KONSUMEN PADA PRODUK KOSMETIK HALAL DI KOTA JAMBI - syafrial syafrial; Firdaus Firdaus (Jurnal Manajemen Terapan dan Keuangan, 2022)
This study aims to determine the direct or indirect effect of the role of social media on consumer buying interest in halal cosmetic products in Jambi City, with consumer perception as an intervening variable. The research sample used was 96 respondents, where data from the sample was collected using a questionnaire and then analyzed by partial least squares path modeling (PLS) technique. The results of the direct influence test prove that: (1) the role of social media and consumer perceptions directly have a significant effect on consumer buying interest in halal cosmetics, and (2) the role of social media directly has a significant effect on consumer perceptions of halal cosmetics. For the mediating effect of the consumer perception variable, it is evident that consumer perception can mediate the indirect effect of the role of social media on consumer buying interest in halal cosmetics.